The Phenomenon of Code-Switching and Mixing in Daily Conversations Among Students of the Religious Program at Darussalam Institute, Ciamis, West Java. - Ahmad Muhammad Basachroh; Umi Kulsum; M Husni T; Cahya Buana; Hadi Yudha Prayoga (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
The aim of this research is to analyze the phenomenon of code-switching and mixing in daily conversations in Arabic-Indonesian between students in the religious program at Darussalam Institute, Ciamis, West Java. This research employed a qualitative descriptive field method. The data consists of students' utterances in daily conversations and the results of interviews. Data were collected through observation and interviews. The research findings showed that there are multiple forms of linguistic switching, both external and internal, which occur through transitions between sentences or phrases depending on the context of communication. Additionally, code mixing was also found in the form of inserting Arabic words, phrases, or terms into sentences in Indonesian, enriching communication and reflecting the comfort and flexibility of the students' language. Factors influencing the occurrence of code-switching and mixing include the characteristics of the speaker, proficiency in Arabic and Indonesian, effective communication needs, formal and informal situations, as well as the presence of the other party and third parties in the interaction. The transition from formal to informal situations also enhances the use of these two phenomena to make communication smoother and easier to understand. These results emphasize that code-switching and mixing are not merely linguistic phenomena but also reflect the social and cultural dynamics in the school environment.